1998
DOI: 10.1111/j.1523-1739.1998.96067.x
|View full text |Cite
|
Sign up to set email alerts
|

Residual Patches and their Contribution to Forest‐Bird Diversity on Northern Minnesota Aspen Clearcuts

Abstract: Managers of upland forest generally operate with the assumption that leaving residual timber in clearcuts is beneficial for wildlife. Our primary objective in this study was to evaluate the contribution of residual patches to forest birds by (1) characterizing differences in components of bird diversity between clearcuts with and without residual patches, (2) characterizing differences in components of bird diversity between residual patches and clearcut edges, and (3) describing any clearcut-wide effects of r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 26 publications
0
10
0
Order By: Relevance
“…However, a detailed review of the large body of literature on effects of retention is beyond the scope of this paper. The following studies provide examples of the benefits of retention on birds and understorey (Merrill et al, 1998;Beese and Bryant, 1999), canopy lichens (Coxson and Stevenson, 2005), aerial insects (Deans et al, 2004), ground-layer bryophytes (Dovčiak et al, 2006), small terrestrial mammals (Gitzen et al, 2007) and saproxylic beetles (Jonsell and Weslien, 2003). Since the retention of structural attributes has not been practised for very long, short-term responses (assumption 1) are documented better than the long-term responses (assumption 2).…”
Section: Retention Of Old-growth Structuresmentioning
confidence: 99%
“…However, a detailed review of the large body of literature on effects of retention is beyond the scope of this paper. The following studies provide examples of the benefits of retention on birds and understorey (Merrill et al, 1998;Beese and Bryant, 1999), canopy lichens (Coxson and Stevenson, 2005), aerial insects (Deans et al, 2004), ground-layer bryophytes (Dovčiak et al, 2006), small terrestrial mammals (Gitzen et al, 2007) and saproxylic beetles (Jonsell and Weslien, 2003). Since the retention of structural attributes has not been practised for very long, short-term responses (assumption 1) are documented better than the long-term responses (assumption 2).…”
Section: Retention Of Old-growth Structuresmentioning
confidence: 99%
“…Many studies have been conducted on responses of wildlife to the retention of mature trees in harvest operations, including a review by Thompson et al (2003) and a meta-analysis by Schieck and Song (2006). Several themes emerge, including that retention of 15-80% of the overstory can maintain habitat for many species found in mature, unharvested stands (Hansen et al, 1995;Schmiegelow et al, 1997;Merrill et al, 1998;Leupin et al, 2004;Schieck and Song, 2006). However, in all of these studies, the bird communities observed in harvested stands always differed from those in unharvested stands.…”
Section: Overstory Retention and Silviculture To Mimic Natural Disturmentioning
confidence: 99%
“…Previous studies have suggested that bird communities in retention forest are not the same as communities in mature or old-growth forest (Merrill et al, 1998;Preston and Harestad, 2007;Atwell et al, 2008). However, studies have also demonstrated that forest patches can provide habitat for at least some forest species (Hansen et al, 1995;Schmiegelow et al, 1997;Seip and Parker, 1997;Merrill et al, 1998;Schieck and Hobson, 2000) although in all of these studies only occupancy or abundance were examined.…”
Section: Introductionmentioning
confidence: 96%
“…However, studies have also demonstrated that forest patches can provide habitat for at least some forest species (Hansen et al, 1995;Schmiegelow et al, 1997;Seip and Parker, 1997;Merrill et al, 1998;Schieck and Hobson, 2000) although in all of these studies only occupancy or abundance were examined. In this study, we compared boreal bird abundance and breeding in residual forest patches with plots of dispersed retention and intact forest during the breeding season.…”
Section: Introductionmentioning
confidence: 97%